Safety and efficacy of low‐power pure‐cut hot snare polypectomy for small nonpedunculated colorectal polyps compared with conventional resection methods: A propensity score matching analysis - Kimura, Hidenori; Oi, Masayuki; Imai, Kenichiro; Imai, Takayuki; Morita, Yukihiro; Nishida, Atsushi; Bamba, Shigeki; Inatomi, Osamu; Andoh, Akira (DEN open, 2025)
Objectives Cold snare polypectomy (CSP) is widely performed for small colorectal polyps. However, small colorectal polyps sometimes include high‐grade adenomas or carcinomas that require endoscopic resection with electrocautery. This study aimed to evaluate the efficacy and safety of a novel resection technique, hot snare polypectomy with low‐power pure‐cut current (LPPC‐HSP) for small colorectal polyps, compared with CSP and conventional endoscopic mucosal resection (EMR). Methods Records of patients who underwent CSP, EMR, or LPPC‐HSP for nonpedunculated colorectal polyps less than 10 mm between April 2021 and March 2022 were retrospectively evaluated. We analyzed and compared the treatment outcomes of CSP and EMR with those of LPPC‐HSP using propensity score matching. Results After propensity score matching of 396 pairs, an analysis of CSP and LPPC‐HSP indicated that LPPC‐HSP had a significantly higher R0 resection rate (84% vs. 68%; p < 0.01). Delayed bleeding was observed in only two cases treated with CSP before matching. Perforation was not observed with either treatment. After propensity score matching of 176 pairs, an analysis of EMR and LPPC‐HSP indicated that their en bloc and R0 resection rates were not significantly different (99.4% vs. 100%, p = 1.00; 79% vs. 81%, p = 0.79). Delayed bleeding and perforation were not observed with either treatment. Conclusions The safety of LPPC‐HSP was comparable to that of CSP. The treatment outcomes of LPPC‐HSP were comparable to those of conventional EMR for small polyps. These results suggest that this technique is a safe and effective treatment for nonpedunculated polyps less than 10 mm.